KAJIAN KONSERVASI EKOSISTEM MANGROVE DI DESA PASAR BANGGI, KABUPATEN REMBANG - Annas, Niharul; Suryono, Suryono; Pribadi, Rudhi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
northern coast of central java. The manage of ecosystem mangrove there started since 1960 with conduct rehabilitation especially independently by the community. The purpose of this research is to study the management of existing mangrove ecosystem conservation and composing the development strategy for conservation area mangrove ecosystem in the Pasar Banggi village. Methods used in this research is descriptive explorative. A method of collecting data by using a method of surveying in the form of primary and secondary data. Data obtained by the kinds of vegetation analyze and SWOT analyze (strength, weakness, opportunity and thread). The results stated that the density of the category tree is worth 2700-3100 ind/ha, Sapling 933-2533 ind/ha, in seedling 83333-100000 ind/ha. The parameters of water quality in the mangrove ecosystem Pasar Banggi suitable for mangrove habitat. The most suitable method of planting is seeds in a polybag. Problems in rehabilitation include biological factors (barnacles, gastropoda and algae), physical factors (wave, wind, sediment, reclamation) and anthropogenic factors (pollution, land conversion, hunting mangrove worms). The presence of community leaders and frequent counseling makes the level of public knowledge about the benefits of mangroves are good. The community participation levels 80%. Rehabilitation is the most common forms of community participation in the Pasar Banggi the rehabilitation are mostly that come from self-help by the community (57.08%) and government assistance or private (42.92%). According to the results of the SWOT analysis, which is a top priority at the Pasar Banggi are: a) Determination of the zone within the mangrove ecosystem conservation (score 4.52) and b) increase the participation of stakeholders on mangrove ecosystem conservation program (score 3.29).